On the evolution of Polish syllabi and core curricula in foreign language teaching - Bielska, Monika (Glottodidactica, 2018)
The first part of the article is devoted to the terminology connected with the notions of core curriculum and syllabi. With reference to the subject, a five-level model of working on documents is presented. After, there follows a historical outline on the evolution of documents, from the national school curriculum to the first core curricula of general education, with reference to foreign language teaching at various stages of education, which was prepared based of the analysis of legal documents. The next chapter shows a syllabus from the present-day perspective of education law, and presents its functions. It describes the results of pilot questionnaires on the functions and role of German teaching syllabi in the Polish educational system in the context of previous theoretical considerations. The article concludes with ideas on leading and optimizing the role of contemporary curricula documents